2005
DOI: 10.1007/s00296-004-0560-z
|View full text |Cite
|
Sign up to set email alerts
|

Digital radiogrammetry as a new diagnostic tool for estimation of disease-related osteoporosis in rheumatoid arthritis compared with pQCT

Abstract: Digital radiogrammetry can precisely estimate severity-dependent cortical reduction of bone mineral density in patients suffering from rheumatoid arthritis both with and without corticoid therapy, and seems to be able to distinguish the side effects of antirheumatic treatment from the disease-related periarticular bone loss. The detection and quantification of periarticular osteoporosis by DXR could be an important diagnostic tool in early rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…This was in accordance with earlier studies using DXA where the RA population was found to have lower total BMD at the distal metacarpal bone [7], at the distal radius [10,12,24], and the hip [11,25,26]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was in accordance with earlier studies using DXA where the RA population was found to have lower total BMD at the distal metacarpal bone [7], at the distal radius [10,12,24], and the hip [11,25,26]. …”
Section: Discussionsupporting
confidence: 93%
“…So far, reduced bone mass at the metacarpal bone shaft in RA has been documented in a number of stud-ies using Digital X-ray Radiogrammetry (DXR) [1,3-5] or at the hand by Dual X-ray Absorptiometry (DXA) [3,6-8]. Trabecular bone loss in RA patients, however, has on-ly been studied at the iliac crest [9] and at the distal radius [10-12], where it was found to be lower in RA patients than in controls [9,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Both the disease and its drug treatment can cause systemic bone loss and also a periarticular disease-related osteoporosis [5]. The periarticular bone loss in hands is an early feature of RA and may precede erosions [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of metacarpal shaft cortical shaft thickness has been demonstrated to be a potentially useful tool for predicting disease progression in RA (4). To date, this measurement has been performed using a commercial system (16). The study reported here employs a novel computer-based method of measuring cortical thickness.…”
Section: Introductionmentioning
confidence: 99%